Therapeutic Use of Dendritic Cells to Promote the Extranodal Priming of Anti-Tumor Immunity - Chen, Lu; Fabian, Kellsye L.; Taylor, Jennifer L.; Storkus, Walter J. (Frontiers in Immunology, 2013)
Ectopic lymphoid tissue, also known as tertiary lymphoid organs (TLO) develop adaptively within sites of chronic tissue inflammation, thereby allowing the host to efficiently crossprime specific immune effector cells within sites of disease. Recent evidence suggests that the presence of TLO in the tumor microenvironment (TME) predicts better overall survival. We will discuss the relevance of extranodal T cell priming within the TME as a means to effectively promote anti-tumor immunity and the strategic use of dendritic cell (DC)-based therapies to reinforce this clinically-preferred process in the cancer-bearing host.